Malocclusion and prematurity at birth. - Cantuaria de Tarso, Marlus; Peixoto , João Cleber (Brazilian Journal of Implantology and Health Sciences, 2021)
Newborns birth prematurely correspond to births with less than 37 weeks of gestation. There are some characteristics intrinsic to the premature ones that act in the Stomatognathic System, triggering the malocclusion. The objective of this article was to investigate the influences that prematurity at birth can generate in a dental environment, more specifically, triggering malocclusion. We searched the databases: Google Scholar and PubMED. In Google Scholar we used the search term: premature birth and malocclusion and dentistry and 2014 and 2015 and 2016 and 2017 and 2018. In PubMED we used the search expression: malocclusion and dentistry and born preterm. It was concluded that, in order to avoid malocclusion, methods of preventive approach in preterm births are necessary to enable adequate growth and development of the stomatognathic system. The encouragement of breastfeeding is related to the influence of breastfeeding, since if it does not occur it can lead to changes in the stomatognathic system.